Endoscopic Fluorescence-Guided Resection Increases Radicality in Glioblastoma Surgery. Issue 1 (6th May 2019) - Bettag, Christoph; Hussein, Abdelhalim; Behme, Daniel; Maragkou, Theoni; Rohde, Veit; Mielke, Dorothee
Abstract: BACKGROUND: Several studies have proven the benefit of a greater extent of resection on progression-free survival and overall survival in glioblastoma (GBM). Possible reasons for incomplete tumor resection might be wrong interpretation of fading fluorescence or overseen fluorescent tumor tissue by a lacking line of sight between tumor tissue and the microscope. OBJECTIVE: To evaluate if an endoscope being capable of inducing fluorescence might overcome some limitations of microscopic fluorescence-guided (FG) resection. METHODS: 5-Aminolevulinic acid (20 mg/kg) was given 4 h before surgery. Microsurgical resection of all fluorescent tissue was performed. Then, the resection cavity was scanned with the endoscope. Fluorescent tissue, not being visualized by the microscope, was additionally removed and histopathologically examined separately. Neuronavigation was used for defining the sites of additional tumor resection. All patients underwent magnetic resonance imaging within 48 h after surgery. RESULTS: Twenty patients with GBM were operated using microscopic and endoscopic FG resection. In all patients, additional fluorescent tissue was detected with the endoscope. This tissue was completely resected in 19 patients (95%). Eloquent localization precluded complete resection in the remaining patient. In 19 patients (95%), histopathological examination confirmed tumor in the additionally resected tissue. In 19 patients (95%), complete resection was confirmed. In all patients, endoscopic FG resection reached beyond the borders of contrast-enhancing tumor. CONCLUSION: Endoscopic FG resection of GBM allows increasing the complete resection rate substantially and therefore is a useful adjunct to microscopic FG resection.